A sociological theory of corporate finance: Societal responsibility and cost of equity in China. Issue 3 (3rd August 2015) - Li, Yuanhui; Foo, Check Teck
Abstract : Purpose: – The paper aims to investigate the relationship between social responsibility and equity in China. In the process, the authors utilize data on corporate social responsibility (CSR) reports (in particular, information disclosure) and equity capital (focusing on cost). The overarching hypothesis may be phrased simply as: is CSR reporting rewarded by the capital market in China? Design/methodology/approach: – The data of 3, 012 list corporations in China securities are used and 1, 015 CSR report quality scores (Rankins CSR Ratings) are hand-gathered from HEXUN (Web site) and utilized in the process of developing the model; financial and stock market information is obtained from the Wind database and the China Stock Market and Accounting Research database. Findings: – The authors' results suggest that overall the quality of CSR report is strongly, negatively related with the cost of capital: the higher the quality of social responsibility information disclosure, the lower the cost of equity capital. Most intriguingly, the authors find a sharp contrast between the government-owned corporations (state-owned enterprises) and privately owned, listed corporations. The quality of CSR reporting has a much higher impact in lowering the cost of equity capital for privately owned corporations. In contrasting the results for mandatory versus voluntary CSR disclosure, the quality of CSR reporting for the latter does not have any higher impact in lowering the cost of equity. Practical implications: – Good social responsibility behavior by corporations and their subsequent information disclosure has beneficial financial impacts. In the authors' research, the authors showed its immediate impact to be in the lowering of the overall corporate cost of equity. In this regard, the authors would recommend that chief executive officers pay more attention to CSR practice and its disclosure. Private firms issuing CSR reports will benefit from much lower financing costs through the capital market. Originality/value: – Due to the structure of capital markets in China, the authors are able to show that CSR reporting of privately owned, listed corporations have much more effective signaling power. On the basis of the authors' empirical findings in relation to the quality of CSR reporting and its impact on cost of capital, the authors suggest there is greater scope for research which takes a "finance and society" perspective. Based on more extensive research, such a perspective may enable scholars to orientate finance and finance research toward a model of "socio-capitalism".